Relationship between tapping frequency of lower limbs and jump abilities in elite Slovak soccer players - Pivovarni, P.; Lacena, M.; Vantner, R. (Sport Science - International Scientific Journal of Kinesiology, 2016)
The aim of the study was to find out the relationship between tapping frequency of lower limbs and vertical jump height in elite Slovak soccer players (n = 41, age = 23.6±4.8 years, height = 180.9±7.1cm, weight = 77.3±7.5kg). The level of tapping frequency of lower limbs (TF) wasdiagnosed by device FiTROtapping, (FiTRONIC, Bratislava, SlovakRepublic). The criterion of performance evaluation of every measured soccer player was total number of contacts with both legs on contact mats of mentioned device during 6 s in a standing position. Vertical jump heights were measured by 2 types of vertical jumps with the device FiTROJumper, (FiTRONIC, Bratislava, Slovak Republic): Squat jump (SJ) a Countermovement jump (CMJ). Pearson correlation coefficient (r, á = 0.05) was used for determination of difference significance between observed parameters (TF - SJ; TF - CMJ). Statistical analysis was realized by software IBM® SPSS® Statistics V19. Statistical analysis showed linear dependency between TF and SJ (r = 0.45, p<0.05) and as well as between TF and CMJ (r = 0.49, p<0.05).